Challenges and potentials of digitalisation for small and mid-sized towns: Proposition of a transdisciplinary research agenda - Jörg Becker; Bettina Distel; Matthias Grundmann; Thomas Hupperich; Norbert Kersting; Andreas Löschel; Marcelo Parreira do Amaral; Hendrik Scholta (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2021)
[Introduction ...] The remainder of this article summarises existing concepts for digital cities, towns, and villages and critically reflects the scope of these concepts (section 2). Section 3 presents selected facets of current research in the area of smart cities and highlights research gaps with regard to smart towns. This section is structured along the concept of liveability as many definitions include increased liveability as a goal of smart initiatives. We conclude this article with some final remarks on future research in this area.
Keywords: 650